2014
DOI: 10.1371/journal.pone.0113329
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Pseudoexfoliation Deposits on the Lens and Their Clinical Correlation- Clinical Study and Review of Literature

Abstract: PurposeTo study the clinical correlates of pattern of deposits over the lens in patients with pseudoexfoliation syndrome (PXF) or pseudoexfoliation glaucoma.MethodsThis retrospective observational study screened 346 patients with PXF seen in glaucoma clinic of a tertiary hospital from 2011–2013. Details like pattern of deposits, location on the lens surface and pupillary abnormalities in slit lamp photographs and their correlation with clinical and demographic variables, were analysed.ResultsA total of 84 eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 28 publications
0
37
1
Order By: Relevance
“…The PXF forms were classified into three clinical phenotypes based on the clinical features described in our earlier study. [ 9 ] Briefly it is as follows- a) Radial pigmentary, RP, form (earlier described pre-granular form)–The clinical features pointing in these eyes would be radial pigments with or without pupillary ruff atrophy. b) RP with classical with early coalescence of pigmentary deposits into the classical form of peripheral exfoliation deposits or combined forms of classical with true exfoliation.c) Classical PXF with dandruff like deposits in the peripheral and /or central area but not restricted to pupillary ruff, lens surface or cornea.Eyes with clinically evident PXF and normal IOP/visual field and optic nerve were classified as those with pseudoexfoliation syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…The PXF forms were classified into three clinical phenotypes based on the clinical features described in our earlier study. [ 9 ] Briefly it is as follows- a) Radial pigmentary, RP, form (earlier described pre-granular form)–The clinical features pointing in these eyes would be radial pigments with or without pupillary ruff atrophy. b) RP with classical with early coalescence of pigmentary deposits into the classical form of peripheral exfoliation deposits or combined forms of classical with true exfoliation.c) Classical PXF with dandruff like deposits in the peripheral and /or central area but not restricted to pupillary ruff, lens surface or cornea.Eyes with clinically evident PXF and normal IOP/visual field and optic nerve were classified as those with pseudoexfoliation syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…In a retrospective observational study performed by Rao, AD. et al [14], out of 346 patients with pseudoexfoliation, the pupillary ruff atrophy was common in all forms of deposition. Rao, A et al [15], conducted a study in which slit-lamp examination identified 16 patients with pupillary ruff atrophy in 32 unilateral pseudoexfoliation cases and 38 of 59 bilateral cases.…”
Section: Discussionmentioning
confidence: 93%
“…Pseudocapsular exfoliation does share some common clinical features with SDC – increased prevalence with age and greater prevalence in males – but in the absence of a known etiology, neither a causal relationship nor common etiological factors appear likely, in spite of the finding of pseudocapsular-like material in extraocular sites, namely the conjunctiva. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%